The influence of vocabulary learning strategies in the development of vocabulary proficiency of sixth graders of Liceo Panamericano School, first quinmester, school year 2018-2019. - Granja Zambrano, Emily Dayana (2018)
This research project was conducted due to the difficulty sixth graders of Liceo Panamericano School faces regarding vocabulary use especially in context. The participants for this study were 27 girls and boys from sixth grade and four English teachers from Liceo Panemericano School. The main objective of the study was to determine which is the influence that vocabulary learning strategies have towards students’ proficieny level. For the creation of the the literature review several sources regarding vocabulary learning strategies application were consulted; nevertheless, there are other factors that affect students’ outcome and use of these vocabulary strategies. A quantitative research was considered for this study, the data gathering instruments applied to the participants was two surveys, a diagnostic test, and an observation sheet during assessment was necessary for this study. It was concluded that even tough teachers use the different vocabulary strategies these might not be as effective for students as expected when students perform in context. Results showed that most of the perceptions of vocabulary learning techniques used in class by both teachers and students match. In addition, the outcomes from the PET test proved that most of the students could not perform as expected since they answered less than half of the section correctly.